DUKUNGAN SOSIAL, STRATEGI KOPING TERHADAP RESILIENSI SERTA DAMPAKNYA PADA KESEJAHTERAAN PSIKOLOGIS REMAJA YANG ORANGTUANYA BERCERAI - Siti Nurhidayah; Agustina Ekasari; Alfiana Indah Muslimah; Ratna Duhita Pramintari; Arini Hidayanti (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
Psychologically, the rate of parental divorce has a negative contribution to child development. Not all children from divorced families have poor psychological well-being. Some children quickly move on with their family conditions so that it does not really affect their psychological well-being. There are at least three factors related to the psychological well-being of children with divorced parents, namely social support, coping strategies and reliance. The purpose of this study was to determine the effect of social support and coping strategies on the psychological well-being of adolescents whose parents divorced through resilience as a mediator. The subjects of this study were 362 (three hundred and sixty two) adolescents who attend school in Bekasi City and Regency which were taken by quota sampling. The data collection technique used six instruments to reveal the characteristics of the subject and family, psychological well-being, social support, coping strategies and resilience. Analysis of individual characteristics using descriptive analysis and a measurement model calledpath analysiswith the help of the SPSS version 23 computer software program.